Hungarian Monitoring, 8 July 1989 . [Magyar rádiófigyelő], 1989. július 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Rude Pravo article criticizes Hungary and Poland - Compilation of international reactions to János Kádár's death - Gorbachev's Paris visit - According to one American TV program, Romanians have the lowest living standards in Europe - West German press opinions on the Warsaw Pact meeting in Bucharest Domestic Affairs: - Unofficial discussions in Bucharest between Ceauşescu and Hungarian delegation led by Rezső Nyers - Bush gives interview to Hungarian journalists - János Kádár: the politician and the man - Summary after latest meeting of three-sided conciliation committee on compromises reached, plans for accelerating discussions and regulation communications - Complications around the Hungarian publication of Solzhenitsyn's "Gulag archipelago" Economy: - Interview with János Martin, government privatization commissioner, on the aims and means of privatization Külpolitika: - A Rude Pravo Magyarországot és Lengyelországot bíráló cikke - Összeállítás Kádár János halálának nemzetközi visszhangjáról - Gorbacsov párizsi látogatása - Egy amerikai TV műsorról, amely szerint a románok élnek a legalacsonyabb életszínvonalon Európában - Nyugatnémet lapvélemények a VSZ bukaresti üléséről Belpolitika - Bukarestben nem hivatalos megbeszélést folytatott a Nyers Rezső vezette magyar delegáció Ceauşescuval - Bush interjút adott magyar újságíróknak - Kádár János mint politikus és mint ember - Összeállítás a háromoldalú egyeztető bizottság legutóbbi ülése után az elért kompromisszumokról, a tárgyalást gyorsító és tájékoztatást szabályozó tervekről - Bonyodalmak Szolzsenyicin Gulag szigetcsoport. című műve magyar kiadása körül Gazdaság: - Interjú Martin Jánossal a kormány privatizálási kormánybiztosával a privatizálás céljárók, módszereiről